Dealing with competitiveness - Middleton, Don. (New York, NY : PowerKids Press : Imprint of Rosen Publishing Group, Incorporated, The, 1999)
Explains competition, its importance, and how to be a good winner as well as a good loser.
Includes index.
620
Accelerated Reader AR
Keywords: Competition (Psychology) in children -- Juvenile literature; Competition (Psychology)